O romance como veículo de preenchimento da falta humana: Reparação de Ian McEwan - Escoza, Cássia [UNESP] (2013)
The nucleus of this study is a reflection concerning the novel Atonement, by Ian McEwan, with the objective of verifying the possibility that this novel constitutes a vehicle for the reparation of human error. As such at first, this study sets out to give an account of the artistic trajectory of the author, with the intention of highlighting Atonement as a synthesis of Ian McEwan’s aesthetic proposals. Next, based on theoretical considerations, the study seeks to identify a possible view of this novel as a link between artistic experience and reality; focusing on the interweaving of discursive strategies and the metalinguistic dimension which discusses the issue of fictional truth. The research goes on to investigate those intertextualities, which attesting to this theme of reparation, and the ways in which they structure the main proposal in the novel. Finally, the research investigates the critical thinking, of the author in the novel concerning issues of man’s place in the world in order to discuss the manner in which social voices are assimilated into the work in focus; and how the novel attempts to condense existential and historical experience so as to transform these into the written word. Thus, the study proposes that the production of meaning for the contemporary world is one of the vital elements in McEwan’s fictional construction